Toward optimization and excellence via a multidisciplinary care model for patients with chronic kidney disease in Spain: The CARABELA-CKD initiative. - Quiroga, Borja; José Gorgojo, Juan; Ignacio Diago, Jesús; Ruiz, Pedro (Nefrología)
The article discusses the CARABELA-CKD initiative in Spain, which aims to optimize and enhance care for patients with chronic kidney disease (CKD) through a multidisciplinary approach. CKD is a significant public health issue in Spain, with a prevalence of 15.1% in adults, influenced by modifiable factors like hypertension, diabetes, and obesity. The initiative involves collaboration between medical societies and aims to standardize CKD care, improve patient outcomes, and reduce the economic burden of the disease. The article outlines the methodology and phases of the initiative, emphasizing the importance of patient-centered care and early intervention to manage CKD effectively.